2022
DOI: 10.1002/14651858.cd013405.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions for treating extracapsular hip fractures in older adults: a network meta-analysis

Abstract: BackgroundHip fractures are a major healthcare problem, presenting a challenge and burden to individuals and healthcare systems. The number of hip fractures globally is rising. The majority of extracapsular hip fractures are treated surgically. ObjectivesTo assess the relative e ects (benefits and harms) of all surgical treatments used in the management of extracapsular hip fractures in older adults, using a network meta-analysis of randomised trials, and to generate a hierarchy of interventions according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 235 publications
0
24
0
Order By: Relevance
“…Dynamic sliding implants such as Dynamic Hip Screw (DHS) or Proximal Femoral Nail Anti‐rotation (PFNA‐II) is the golden standard in trochanteric fractures as it did yield a lower risk of unplanned return to theater 14 . However, excessive sliding or femoral medialization of those implants is a risk factor for implant failure 15 and is a unique complication that occurs almost exclusively in the treatment of unstable trochanteric fractures with cephalomedullary nailing 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic sliding implants such as Dynamic Hip Screw (DHS) or Proximal Femoral Nail Anti‐rotation (PFNA‐II) is the golden standard in trochanteric fractures as it did yield a lower risk of unplanned return to theater 14 . However, excessive sliding or femoral medialization of those implants is a risk factor for implant failure 15 and is a unique complication that occurs almost exclusively in the treatment of unstable trochanteric fractures with cephalomedullary nailing 16 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Dynamic sliding implants such as Dynamic Hip Screw (DHS) or Proximal Femoral Nail Anti-rotation (PFNA-II) is the golden standard in trochanteric fractures as it did yield a lower risk of unplanned return to theater. 14 However, excessive sliding or femoral medialization of those implants is a risk factor for implant failure 15 and is a unique complication that occurs almost exclusively in the treatment of unstable trochanteric fractures with cephalomedullary nailing. 16 Law et al found that intramedullary nailing of unstable intertrochanteric fractures is inherently predisposed to femoral neck element medial migration making it more susceptible to consequent cut-out compared to fixation with the DHS.…”
Section: Introductionmentioning
confidence: 99%
“…2 Randomized controlled trials of SHS versus IMN, systematic reviews, registry data, and guidelines all inform implant selection. 1,[3][4][5][6][7][8] SHS and IMN (which may be short or long) are comparable for most (AO, A1, and A2) extracapsular trochanteric fractures. 1 Despite this, many patients with these fractures are treated with IMN.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8] SHS and IMN (which may be short or long) are comparable for most (AO, A1, and A2) extracapsular trochanteric fractures. 1 Despite this, many patients with these fractures are treated with IMN. [9][10][11] This is important as SHS are considerably more cost-effective, and implant costs have a positive linear association with overall inpatient cost of care.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Most recently, two network meta-analyses including over 100 randomized controlled trails have showed that the 1-year mortality rates were as high as 23.5% and 20.2% in patients with intracapsular and extracapsular hip fracture, respectively. 20 , 21 This increased mortality risk persisted for more than two decades after hip fracture. 22 Due to the advanced age of hip fracture patients, the prevalence of widowhood is relatively high, such as 46.2% in Sweden, 23 43.1% in USA, 24 42.6% in Denmark, 25 and 39.2% in Norway.…”
Section: Introductionmentioning
confidence: 99%